A Mean Value Related to Primitive Roots and Golomb’s Conjectures - Weiqiong Wang; Wenpeng Zhang (Abstract and Applied Analysis)
The main purpose of this paper is using the properties of Gauss sums and the estimate for character sums to study a mean value problem related to the primitive roots mod p and the different forms of Golomb’s conjectures and propose an interesting asymptotic formula for it.